IMDEX Asia 2015 coast guards in the South China Sea : proxy fighters? - Bitzinger, Richard A. (2015)
Para-naval forces, particularly Coast Guards, are increasingly active in the South China Sea when it comes to enforcing maritime rights. These so-called “white-hulled” fleets are more and more serving as proxies for naval forces, ratcheting down confrontations at sea. This may not last forever, however.